Analisis Siklus Penjualan dan Penagihan: Studi Literatur pada PT Unilever Tbk tahun 2024 - St. Nabila Ramadhani S; Keisya Nur Ramadhani; Rahma Fatimah Malik; M. Indra Irwan; Fina Ruzika Zaimar (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2026)
The Fast Moving Consumer Goods (FMCG) industry makes a significant contribution to supporting the national economy, with PT Unilever Indonesia Tbk being one of the companies holding a dominant position in the market. This study focuses on evaluating the effectiveness of Unilever's sales and billing cycle in 2024 using a literature review method through a Systematic Literature Review (SLR) approach. Data were collected from journals, annual reports, and other relevant scientific sources over the past ten years. The review results show a significant improvement in billing performance, reflected in an increase in receivable turnover from 9.77 times (2022) to 16.64 times (2024), as well as a decrease in days sales outstanding (DSO) from 37.37 days to 21.94 days. This improvement is linked to the strengthening of internal control systems, the implementation of digital technologies such as e-invoicing and artificial intelligence, and compliance with PSAK 71 on Expected Credit Loss (ECL). Effective accounts receivable management through balanced credit policies is crucial for maintaining cash flow, boosting profitability, and preserving the company's competitiveness in the competitive FMCG industry.